(untitled) (Contemporary Mathematics, 2024)
In this article, we will use a weighted regular matrix formed by Leonardo numbers and variable exponent sequence spaces to build a new stochastic space. We have proposed various geometric and topological structures for this new space, as well as the multiplication operator that operates on it.